ANALISIS KEBUTUHAN UNTUK MEMBANGUN MEDIA PEMBELAJARAN MAYA YANG MENDUKUNG PROYEK ENERGI BARU DAN TERBARUKAN: ANALISIS KEBUTUHAN PENGGUNA - Ariana Yunita; Meredita Susanty; Galang Amanda Dwi Pamungkas; Herminarto Nugroho (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2019)
Energy security has become the main issue for Indonesia Government because Indonesia is targeted to be independent in energy field.To reach the goals NRE usage, there should be cooperations amongst all party : government, society, academicians as well as corporates. Virtual Learning Environment (VLE) is a powerful application to deliver knowledge in the digital age while contributes to educate society about New and Renewable Energy (NRE). However, user requirements are needed before developing VLE to reveal existing conditions and understand the users’ behaviour. This paper purposes to understand the user requirements, who are university students, to contribute to NRE project. Research methods used are interview, observation and questionnaire. Interview was conducted with Lentera Bumi Nusantara who develops NRE technology especially wind turbine in Indonesia. Observation was done in Lentera Bumi Nusantara’s office and questionnaire was distributed amongst 92 students in Universitas Pertamina, Jakarta, Indonesia. The results show that university students are human resources needed in NRE project. Then, learning materials regarding how to build blade and wind turbine have not distributed to others. Furthermore, results show that 84% of university students are ready to contribute in NRE project. However, only 37% of university students own original idea for NRE project related to their academic background. To build the VLE to support NRE projects, there should be menu for university students to discuss online so they can share ideas regarding NRE and menu for contributing to NRE project in Indonesia.